Placental Ras Regulates Inflammation Associated with Maternal Obesity - Stella Liong; Gillian Barker; Martha Lappas (Hindawi Limited, 2018)
Heightened placental inflammation and dysfunction are commonly associated in pregnant obese women compared to their pregnant lean counterparts. The small GTPase superfamily members known as the rat sarcoma viral oncogene homolog (Ras) proteins, in particular, the K-Ras and H-Ras isoforms, have been implicated to regulate inflammation. The aims were to determine the placental Ras expression and activity with maternal obesity and its role in regulating placental inflammation. Human placenta was obtained at term Caesarean section from lean and obese pregnant women to determine the effect of maternal obesity on Ras protein expression and activity. To determine the effect of Ras on inflammation induced by bacterial endotoxin LPS and proinflammatory cytokines TNF-α or IL-1β, the chemical inhibitor lonafarnib (total Ras inhibitor) and siRNA (siKRAS and siHRAS) were used. Total Ras protein expression together with combined K-Ras and H-Ras activity was significantly increased in the placenta of obese pregnant women and when stimulated with LPS, IL-1β, or TNF-α. Lonafarnib significantly suppressed LPS-, IL-1β-, or TNF-α-induced IL-6, IL-8, MCP-1, and GRO-α expression and secretion in placental tissue. Primary trophoblast cells transfected with siKRAS or siHRAS demonstrated only K-Ras silencing significantly decreased IL-1β-, TNF-α-, or LPS-induced IL-6, IL-8, and MCP-1 expression and secretion. Furthermore, siKRAS significantly reduced downstream ERK-1/2 activation induced by LPS. In trophoblast cells, ERK-1/2 signalling is required for IL-6, IL-8, MCP-1, and GRO-α secretion. These studies implicate a role for K-Ras in regulating inflammation in human placenta. Suppressing overactive placental K-Ras function may prevent adverse fetal outcomes complicated by maternal obesity.